The monkey [videorecording (Blu-Ray)] - King, Stephen, 1947- (Decal, 2025)
When twin brothers Bill and Hal find their father's old monkey toy in the attic, a series of ghastly deaths commence. The brothers decide to throw the toy away and move on with their lives, growing apart over the years.